Continuous multistep synthesis of 2-(azidomethyl)oxazoles - Rossa, Thaís A.; Suveges, Nícolas S.; Sá, Marcus M.; Cantillo, David; Kappe, C. Oliver (Beilstein Journal of Organic Chemistry, 2018)
An efficient three-step protocol was developed to produce 2-(azidomethyl)oxazoles from vinyl azides in a continuous-flow process. The general synthetic strategy involves a thermolysis of vinyl azides to generate azirines, which react with bromoacetyl bromide to provide 2-(bromomethyl)oxazoles. The latter compounds are versatile building blocks for nucleophilic displacement reactions as demonstrated by their subsequent treatment with NaN3 in aqueous medium to give azido oxazoles in good selectivity. Process integration enabled the synthesis of this useful moiety in short overall residence times (7 to 9 min) and in good overall yields.
Keywords: azirines; continuous flow; heterocycles; oxazoles; process integration; vinyl azides

(untitled) - Ibrar, A.; Khan, I.; Abbas, N.; Farooq, U.; Khan, A. (RSC Adv., 2016)

(untitled) - Hassner, A.; Fischer, B. (Heterocycles, 1993)

(untitled) - Yeh, V. S. C. (Tetrahedron, 2004)

(untitled) - Naik, S. R.; Harindran, J.; Varde, A. B. (J. Biotechnol., 2001)

(untitled) - Kunze, B.; Jansen, R.; Pridzun, L.; Jurkiewicz, E.; Hunsmann, G.; Höfle, G.; Reichenbach, H. (J. Antibiot., 1992)

(untitled) - Greenblatt, D. J.; Matlis, R.; Scavone, J. M.; Blyden, G. T.; Harmatz, J. S.; Shader, R. I. (Br. J. Clin. Pharmacol., 1985)

(untitled) - Wang, R.; Dasgupta, A.; Ward, M. M. (Ann. Rheum. Dis., 2016)

(untitled) - Crawford, P. F.; Crawley, K. R.; Tucker, H. A. (J. New Drugs, 1961)

(untitled) - Chowdhury, S. R.; Chauhan, P. S.; Dedkova, L. M.; Bai, X.; Chen, S.; Talukder, P.; Hecht, S. M. (Biochemistry, 2016)

(untitled) - Boger, D. L. (Chem. Rev., 1986)

(untitled) - Turchi, I. J.; Dewar, M. J. S. (Chem. Rev., 1975)

Oxazoles: Synthesis, Reactions, and Spectroscopy, Part A - Levin, J. I.; Laakso, L. M. (Oxazole Diels–Alder Reactions, 2003)

(untitled) - Blond, G.; Gulea, M.; Mamane, V. (Curr. Org. Chem., 2016)

(untitled) - Firestone, R. A.; Harris, E. E.; Reuter, W. (Tetrahedron, 1967)

(untitled) - Dumond, Y. R.; Gum, A. G. (Molecules, 2003)

(untitled) - Bresciani, S.; Tomkinson, N. C. O. (Heterocycles, 2014)

(untitled) - Bredereck, H.; Gompper, R. (Chem. Ber., 1954)

(untitled) - Gompper, R.; Christmann, O. (Chem. Ber., 1959)

(untitled) - Ritson, D. J.; Spiteri, C.; Moses, J. E. (J. Org. Chem., 2011)

(untitled) - Fischer, E. (Ber. Dtsch. Chem. Ges., 1896)

(untitled) - Ingham, B. H. (J. Chem. Soc., 1927)

(untitled) - Kotani, E.; Kobayashi, S.; Adachi, M.; Tsujioka, T.; Nakamura, K.; Tobinaga, S. (Chem. Pharm. Bull., 1989)

(untitled) - Ishiwata, Y.; Togo, H. (Tetrahedron, 2009)

(untitled) - Ning, Y.; Otani, Y.; Ohwada, T. (J. Org. Chem., 2017)

(untitled) - Brahma, S.; Ray, J. K. (J. Heterocycl. Chem., 2008)

(untitled) - Sauers, R. R.; Hagedorn, A. A., III; Van Arnum, S. D.; Gomez, R. P.; Moquin, R. V. (J. Org. Chem., 1987)

(untitled) - Zeng, T.-T.; Xuan, J.; Ding, W.; Wang, K.; Lu, L.-Q.; Xiao, W.-J. (Org. Lett., 2015)

(untitled) - Fowler, F. W.; Hassner, A. (J. Am. Chem. Soc., 1968)

(untitled) - Hassner, A.; Burke, S. S.; I, J. C. (J. Am. Chem. Soc., 1975)

(untitled) - Smith, A. B., III; Minbiole, K. P.; Freeze, S. (Synlett, 2001)

(untitled) - Linder, J.; Blake, A. J.; Moody, C. J. (Org. Biomol. Chem., 2008)

(untitled) - Kuntiyong, P.; Lee, T. H.; Kranemann, C. L.; White, J. D. (Org. Biomol. Chem., 2012)

(untitled) - Patil, P. C.; Luzzio, F. A. (Tetrahedron Lett., 2016)

(untitled) - Patil, P. C.; Tan, J.; Demuth, D. R.; Luzzio, F. A. (Bioorg. Med. Chem., 2016)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

(untitled) - McQuade, D. T.; Seeberger, P. H. (J. Org. Chem., 2013)

(untitled) - Ahmed-Omer, B.; Barrow, D. A.; Wirth, T. (ARKIVOC, 2011)

(untitled) - Cludius-Brandt, C.; Kupracz, L.; Kirschning, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Cantillo, D.; Gutmann, B.; Kappe, C. O. (Org. Biomol. Chem., 2016)